Storytelling: Online Stories and Public Consciousness - Nikita N. Ravochkin; Anis Henchiri (Виртуальная коммуникация и социальные сети, 2023)
Online stories posted in domestic and foreign social networks are a special case of storytelling, i.e., a method of transmitting information as a visual or audio-visual personal and subjective narrative that presupposes no mutual correspondence between this subjective knowledge and reality. The article describes theoretical approaches to the study of online narrative as a tool for influencing public consciousness. The authors used such methods as the analysis of secondary sources, empirical observation, and description to study online stories published in Russian and foreign social networks. Interdisciplinary scientific literature made it possible to draw a number of conclusions about the significant influencing potential of this type of storytelling. The genre relies on emotional impact: stories are short, convenient, and clear enough to represent large amounts of information and axiological attitudes. The narrative nature of the phenomenon provides both the fascination of the content consumed and the depth of its cognitive and behavioral influence on the imaginary communities of modern society and their individual representatives.